2021
DOI: 10.3171/2020.6.spine20751
|View full text |Cite
|
Sign up to set email alerts
|

A long-term follow-up study of spinal abnormalities and pain in adults with cerebral palsy and spastic diplegia more than 25 years after selective dorsal rhizotomy

Abstract: OBJECTIVEThe main purpose of selective dorsal rhizotomy (SDR) is to reduce spasticity in the lower extremities of children diagnosed with cerebral palsy (CP) and spastic diplegia. The potential for developing spinal abnormalities and pain is a concern, especially in the aging CP population. Therefore, the aim of this study was to evaluate spinal abnormalities, level of pain, and disability (due to back or leg pain) in adults with CP, and associations with participant characteristics, more than 25 years after S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Nonetheless, the MAS score was available for all studies and showed SDR to be a good and valid option for nonambulatory patients. 24,26,31,32 This finding is consistent with previous reports focusing on ambulatory patients (GMFCS levels I-III) undergoing SDR and underlines its effectiveness even in high-level patients. 2,12,24,28,[33][34][35] Another important and evolving tool for the outcome of a treatment is the implementation of PROMs and scores addressing the quality of life not only of the patients, but also of the caregivers.…”
Section: Palliative Single-level Sdr: a Valid Treatment Option For Pa...supporting
confidence: 92%
See 1 more Smart Citation
“…Nonetheless, the MAS score was available for all studies and showed SDR to be a good and valid option for nonambulatory patients. 24,26,31,32 This finding is consistent with previous reports focusing on ambulatory patients (GMFCS levels I-III) undergoing SDR and underlines its effectiveness even in high-level patients. 2,12,24,28,[33][34][35] Another important and evolving tool for the outcome of a treatment is the implementation of PROMs and scores addressing the quality of life not only of the patients, but also of the caregivers.…”
Section: Palliative Single-level Sdr: a Valid Treatment Option For Pa...supporting
confidence: 92%
“…13,21,25 When SDR was first developed and applied in 1987 by Peacock, it gained much popularity for spasticity treatment and remained the standard surgical technique for more than 30 years, exposing spinal roots via multilevel access from the conus medullaris down to S2, with slight modifications over time. 8,26,27 Considering the higher periand postoperative risks of multilevel SDR such as spinal deformity, CSF leaks, and severe infections, this procedure was initially reserved for GMFCS level I-III patients with the aim of maintaining or improving ambulation. 27 The single-level interlaminar approach or single-level laminotomy/laminoplasty approaches are less invasive and used more frequently nowadays, causing fewer postoperative spinal deformities or instabilities and fewer CSF fistulas.…”
Section: Palliative Single-level Sdr: a Valid Treatment Option For Pa...mentioning
confidence: 99%
“…In addition, 28% of adults with CP experience pain daily. 10 Park et al reported a single laminectomy at the conus level. 3 This technical improvement significantly reduced the incidence of spinal deformities.…”
Section: Discussionmentioning
confidence: 99%